Therapeutic Efficacy of Intravesical Platelet-Rich Plasma Injections for Interstitial Cystitis/Bladder Pain Syndrome—A Comparative Study of Different Injection Number, Additives and Concentrations - Jiang, Yuan-Hong; Jhang, Jia-Fong; Lin, Teng-Yi; Ho, Han-Chen; Hsu, Yung-Hsiang; Kuo, Hann-Chorng (Frontiers in Pharmacology, 2022)
Purpose: Intravesical platelet-rich plasma (PRP) injections have been demonstrated effective in relieving symptoms among patients with interstitial cystitis/bladder pain syndrome (IC/BPS). This study compared the clinical efficacy among different injection number, adding solution, and concentrations of PRP. Methods: A total of 63 patients with IC/BPS were enrolled and randomly allocated to four subgroups who received single high-dose PRP (from 100 mL whole blood) plus 10 mL of normal saline or plasma injected over 20 or 40 sites. Patients were followed up at 1, 3, and 6 months for changes in the IC symptom index (ICSI) and problem index (ICPI), visual analog scale (VAS), global response assessment (GRA), and urodynamic parameters. Furthermore, we compared the clinical outcome with our previous study in a group of 55 IC/BPS patients who underwent four monthly low-dose PRP (from 50ml whole blood) injections. Results: The result of this study showed significant improvements in IC symptoms (ICSI 11.9±4.4 vs 10.2±4.9, p=0.009; ICPI 12.3±3.4 vs 10.6±4.7, p=0.003); VAS (5.46±2.96 vs 3.83±3.1, p 0.000), and maximum flow rate (10.4±4.9 vs 17.1±11.5 ml/s, p=0.000) at 3 months after single high-dose PRP injection. However, no significant differences in therapeutic results were observed among subgroups, regardless of the added component or injecting site. The improvements of ICSI, ICPI, and GRA at 6 months were lower in comparison with the results of four low-dose PRP injections. All patients were free of dysuria, urinary retention, or urinary tract infection after PRP treatment. Conclusion: Intravesical PRP injection is effective for IC/BPS. The addition of normal saline or plasma and injection site had no influence on therapeutic efficacy. However, the symptom improvement and GRA after a single high-dose PRP injection was lower than that after four low-dose PRP injections 6 months after the first treatment. Limitation of the study is lack of sham control group.